Social Security Hearings and Appeals Office Staff in Halloween Costumes - Watkins, Howard::::::::: (1984)
Staff members in individual costumes; witches, surgeon, pumpkin, Groucho Mark, clown, yellow crayon, puppy, nurses, transvestite, blue people